Rethinking difference in music scholarship - Bloechl, Olivia Ashley; Lowe, Melanie Diane 1969-; Kallberg, Jeffrey 1954- (Cambridge University Press, 2015)
Two decades after the publication of several landmark scholarly collections on music and difference, musicology has largely accepted difference-based scholarship. This collection of essays by distinguished contributors is a major contribution to this field, covering the key issues and offering an array of individual case studies and methodologies. It also grapples with the changed intellectual landscape since the 1990s. Criticism of difference-based knowledge has emerged from within and outside the discipline, and musicology has had to confront new configurations of difference in a changing world. This book addresses these and other such challenges in a wide-ranging theoretical introduction that situates difference within broader debates over recognition and explores alternative frameworks, such as redistribution and freedom. Voicing a range of perspectives on these issues, this collection reveals why differences and similarities among people matter for music and musical thought
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Gesellschaft; Musik; Difference (Philosophy) in music; Music / Social aspects; Music / Philosophy and aesthetics; Gender identity in music; Music and race; Differenz; Musikphilosophie; Musikwissenschaft; Geschichte; Geschlechterrolle; Aufsatzsammlung